2012
DOI: 10.1007/s00122-012-1871-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci conferring resistance to rice black-streaked virus in maize (Zea mays L.)

Abstract: Maize rough dwarf disease (MRDD) is one of the most serious virus diseases of maize worldwide, and it causes great reduction of maize production. In China, the pathogen was shown to be rice black-streaked virus (RBSDV). Currently, MRDD has spread broadly and leads to significant loss in China. However, there has been little research devoted to this disease. Our aims were to identify the markers and loci underlying resistance to this virus disease. In this study, segregation populations were constructed from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Laodelphax striatellus Fallen Bai et al 2002;Zhang et al 2001;Fang et al 2001;Luan et al 2012). Yield losses of 30-100 % can be caused in severely infected fields yearly (Bai et al 2002;Shi et al 2012a).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Laodelphax striatellus Fallen Bai et al 2002;Zhang et al 2001;Fang et al 2001;Luan et al 2012). Yield losses of 30-100 % can be caused in severely infected fields yearly (Bai et al 2002;Shi et al 2012a).…”
Section: Introductionmentioning
confidence: 95%
“…In the past, various studies have focused on mapping QTLs for MRDD resistance based on linkage mapping, using bi-parental mapping populations such as F 2 , BC 1 and RIL populations, and many QTLs have been detected for MRDD resistance (Shi et al 2012a;Chen et al 2008;Luan et al 2012;Shi et al 2012b;Tao et al 2013). However, the detected QTLs were only partially consistent across the few mapping populations analyzed, which suggests that the genetic background of the studied population has a strong influence, and because of the few recombination events, large confidence intervals for QTLs and restricted alleles in the bi-parental genotypes, very few have been incorporated into maize resistance breeding programs (Van Inghelandt et al 2012;Riedelsheimer et al 2012b;Gupta et al 2005;Cardon and Bell 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. At the distal end of the chromosome, QTLs for resistance to two maize-infecting fijiviruses and to the unrelated MCDV and MSpV were identified using different population structures and unrelated germplasm (Di Renzo et al, 2004;Luan et al, 2012;Martin et al, 2010;Zambrano, Jones, Brenner, et al, 2014). Overlapping QTLs for the nucleorhabdoviruses MMV and MFSV were identified in the inbred line Oh1VI in bin 2.08 (Zambrano, Jones, Brenner, et al, 2014).…”
Section: Genetics Of Resistance To Virus Diseasesmentioning
confidence: 99%
“…Because MRDV and RBSDV are obligately transmitted by vectors, identification and development of highly resistant lines, hybrids, and cultivars have been slow. However, recent studies have identified strong quantitative trait loci (QTLs) for resistance in diverse germplasm (Luan, Wang, Li, Zhang, & Zhang, 2012;Shi et al, 2012;.…”
Section: Maize Rough Dwarfmentioning
confidence: 99%